Build It - Elliott, Glenn; Corey, Debra (Ascent Audio, 2019)
Companies with the best cultures generate stock market returns of twice the general market and enjoy half the employee turnover of their peers. Their staff innovate more, deliver better customer service and, hands-down, beat the competition. These companies outperform and disrupt their markets. They break the rules of traditional HR, they rebel against the status quo. Build It has found these rebels and the rulebreakers. From small startups to global powerhouses, this book shows that courage, commitment and a people-centric mindset, rather than money and resources, are what you need to turn an average business into a category leader. The book follows the clear and proven Engagement Bridge model, developed from working with thousands of leading companies worldwide on their own employee engagement journeys. The practical model highlights the areas that leaders need to examine in order to build a highly engaged company culture and provides a framework for success.